Security Aspects in Online Purchasing Applications - Tariq, Kanar R.; Bakhtyar, Ribwar; Forsyth, David I.; Johni, Riyam A. (Kurdistan Journal of Applied Research, 2017)
Motivations to engage in retail shopping comprise both utilitarian and hedonic dimensions. Business to consumer e-commerce conducted via the mechanism of web-shopping offers an expanded opportunity for companies to create a cognitively and esthetical good shopping environment in ways not readily imitable in the no electronic shopping world. In this report the details key implementation aspects of a typical online purchasing system, hypothetically labeled SYSTEM X, and describe how it works - particularly regarding security issues. The report concludes with recommendations for users of similar online buying systems.